A comparative study of quality of life of elderly living in old age homes and within family - Soni, Anamika; Lodha, Rama S. (International Journal Of Community Medicine And Public Health, 2024)
Background: The traditional family structure in India, which historically offered support to the elderly within joint families, is transforming with the disintegration of such setups. Consequently, the concept of old age homes (OAHs) is gaining traction, and there is a notable surge in individuals turning to OAHs care. Despite this trend, there is limited knowledge about the quality of life (QOL) experienced by the Indian elderly residing in OAHs. Objectives was to understand why the elderly transition to OAHs and compare their QOL concerning physical, psychological, social support and environmental health with those living with family. Methods: In a cross-sectional study, elderly individuals aged above 60 years were examined. Following the acquisition of written consent and the matching process for age, sex, and socioeconomic status, 100 elderly individuals from OAHs and 200 elderly individuals living within family setups were randomly selected for inclusion in the study. WHOQOL-BREF questionnaire was used to assess quality of life. Results: The study revealed that the physical (40.9) and environmental (35) domains were relatively more favourable for the elderly living with their families. In contrast, the social (55.7) and psychological (51.3) domains showed better outcomes (p<0.05) for elderly residing in OAHs. Conclusions: Though Family plays a crucial role in influencing various domains of health, in situations where traditional family structures may not be present, efforts to enhance the structure of OAHs can contribute to improving the QOL for individuals.